PEMANFAATAN AKUN PEMBELAJARAN UNTUK KOLABORASI PENDIDIK DAN TENAGA KEPENDIDIKAN DALAM IMPLEMENTASI PROGRAM SEKOLAH PENGGERAK - Tintin Kartini (PGSD Universitas Muhammadiyah Cirebon, 2022)
One of the characteristics emphasized by Program Sekolah Penggerak (Motivating School Program) is collaboration among stakeholders at the Ministry/Agency level, Regional Government, human resources in education units and also partners. The digitization of schools and various applications and platforms are parts of the support system for the implementation of the Independent Curriculum at schools. Utilization of information technology-based learning tools, applications and platforms is strongly encouraged as an effort to present differentiated and learner-centered learning. The provision of Akun Pembelajaran (learning accounts) by the Government for educators, education staff, and students from ECCE, primary and secondary education levels, makes it easier for educators and staffs to collaborate in providing educational services. This study was conducted to find out how the use of learning accounts can optimize the collaboration in the implementation of PSP. The research was conducted with a qualitative approach using the documentation study method which was carried out by literature review and observation. The results showed that the activation of learning accounts for educators and education staff for elementary school levels in the districts/cities implementing PSP Batch 1 was high, namely 93% for educators and 89.8% for education staff. Learning accounts provide a great opportunity for them to collaborate by utilizing the accounts in accessing various platforms and collaborating in planning and implementing the learning process. Keywords: Independent Curriculum, learning account, collaborative learning